Silicon-based negative pole piece and preparation method thereof

By adopting a double coating structure in the silicon -based pole chips, the adhesion mechanism of polyacryonic acid and its alkali salt is used to solve the edge analysis of lithium effects and volume expansion of the lithium -ion battery in the lithium -ion battery, and the battery is realized, and the battery is achieved. High -cycle stability and low pollution risk.

CN119381401AActive Publication Date: 2025-01-28ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411383932.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The silicon-based negative electrode sheet in lithium-ion batteries has an edge lithium-ion effect, which leads to a decrease in battery capacity and safety risks. The volume expansion of the silicon-based material during charging and discharging, resulting in rupture and generation of SEI film, further limiting the silicon-based material in the battery. Development in industry.

Method used

The silicon -based pole chip with a double coating structure is used. Among them, the first coating uses polyacryonic acid as a binder, and the second coating uses the alkali salt of polyacrylate as a binder. The carboxyl group between the hydroxide group and the polyacryonic acid formation of hydrogen bonds or covalent bonds to enhance the adhesion between the silicon particles and the collector, alleviate the stress caused by the volume change, and inhibit the lithium analysis of the edge.

Benefits of technology

Effectively suppress the marginal lithium analysis of the negative chip of the silicon base, improve the cycle stability and integrity of the battery, reduce the risk of the battery pollution, and improve the battery's multiplier and resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381401A_ABST
    Figure CN119381401A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-based negative pole piece and a preparation method thereof.The silicon-based negative pole piece comprises a current collector, a first coating and a second coating are arranged on the same surface of the current collector, the first coating is located on the two sides of the second coating, the first coating is coated with first negative pole slurry, and the second coating is coated with second negative pole slurry; the first negative electrode slurry comprises polyacrylic acid, and the second negative electrode slurry comprises alkali salt of polyacrylic acid. The silicon-based negative pole piece provided by the invention has the advantages of less pollution, low fringe effect or no fringe effect and small volume change in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a silicon-based negative electrode plate and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics and power fields due to their high energy density, fast charging capability and high safety. However, with the iteration and update of technology, people have higher and higher requirements for the fast charging performance, battery capacity and other battery performance of lithium-ion batteries. In fast-charging batteries, due to the edge effect and edge interface problems of the battery pole piece, the speed of the battery cell to extract and extract lithium ions at the edge is faster than that of the main area (i.e., the middle area), and the battery cell is prone to lithium deposition at the edges of the pole piece on both sides, resulting in safety problems such as battery capacity reduction and even short circuit fire. In addition, for silicon-based negative electrode lithium-ion batteries, in addition to the problem of lithium deposition causing battery capacity reduction, although the silicon-based negative electrode configured has the highest theoretical specific capacity, the volume of silicon will expand violently during the battery charging and discharging process, which will cause the SEI film to repeatedly rupture and form on the electrode surface. This causes the silicon negative electrode to experience a sharp capacity decay and further lithium deposition during the battery lithium insertion and extraction cycle, and will cause the silicon-based material coating to fall off, which to a large extent limits the further development of silicon-based materials in the battery industry.

[0003] The Chinese patent with publication number CN117199291A discloses a negative electrode active slurry, a battery negative electrode plate and a lithium-ion secondary battery. The raw material components of the negative electrode active slurry include: a silicon-based negative electrode material and an inorganic lithium compound; wherein the inorganic lithium compound can react with active lithium to form a protective layer. Among the raw material components, the silicon-based negative electrode material, as an active material component in the battery, can undergo electrochemical reactions during the charging and discharging process and is the source of energy in the battery; and a very small amount of inorganic lithium compound additives are added to the negative electrode slurry, which can react to form a solid protective layer during the charging and discharging process, reduce the growth of lithium dendrites, thereby inhibiting the occurrence of lithium precipitation on the negative electrode surface, and thereby extending the cycle life of the silicon-based negative electrode. However, the added inorganic lithium compound is toxic, and because it is easily dissolved in the electrolyte, it is easy to cause pollution problems after leakage. Summary of the invention

[0004] One of the purposes of the present invention is to provide a silicon-based negative electrode plate with less pollution during use and low edge lithium deposition effect.

[0005] In order to achieve the above-mentioned purpose, the present invention provides a silicon-based negative electrode plate, which includes a current collector, and the same surface of the current collector is provided with a first coating and a second coating along the Y direction, the first coating is located on both sides of the second coating, the first coating is coated with a first negative electrode slurry, and the second coating is coated with a second negative electrode slurry, the first negative electrode slurry includes polyacrylic acid, and the second negative electrode slurry includes an alkali salt of polyacrylic acid.

[0006] The silicon-based negative electrode plate provided by the present invention, wherein the alkaline hydroxyl groups in the alkaline salt of polyacrylic acid can neutralize the carboxyl groups agglomerated in the polyacrylic acid, the carboxyl functional groups can generate hydrogen bonds or covalent bonds with the groups on the silicon surface, can enhance the bonding between silicon particles and between silicon particles and the current collector, the high flexibility of the main chain enables it to withstand the stress caused by the volume change during the lithium extraction and insertion of the silicon-based material, relieve the volume change of the silicon-based material, and is not prone to the shedding of active materials and the cracking of the pole piece, thereby ensuring the stability and integrity of the silicon electrode during the cycle. In addition, the bond formed by the carboxyl group of polyacrylic acid and the silicon-based material, because the carboxyl functional group directly generates hydrogen bonds or covalent bonds with the silicon surface groups, produces a better effect than with polyacrylic acid, which results in a smaller volume change of the second coating, and the lithium ion transmission efficiency of the first coating is lower than the lithium ion transmission efficiency of the second coating, that is, the lithium ion insertion speed of the first coating is lower than the lithium ion insertion speed of the second coating, so the edge lithium precipitation effect of the first coating is suppressed. Since the alkali salt of polyacrylic acid is a low-toxic or non-toxic substance, and polyacrylic acid and the alkali salt of polyacrylic acid are high-molecular substances, they are not easily dissolved in the electrolyte during use but exist in the form of colloid or gel, and there is less pollution during use.

[0007] Furthermore, the head-to-tail lithium deposition coefficient k of the silicon-based negative electrode plate satisfies the relational expression I, which is as follows:

[0008]

[0009] r1 is the ratio of the thickness d1 of the first coating layer to the thickness d2 of the second coating layer; r2 is the ratio of the width w1 of the first coating layer to the width w2 of the second coating layer, W1 is the addition ratio of the binder in the first negative electrode slurry, and W2 is the addition ratio of the binder in the second negative electrode slurry. When k>0, the electrode will not have the head-tail lithium deposition phenomenon. When k≤0, there is a risk of head-tail lithium deposition, and the smaller the k value, the greater the risk of head-tail lithium deposition abnormality.

[0010] When the head-to-tail lithium deposition coefficient is within the range disclosed in the technical solution of the present invention, the edge effect completely disappears, and the inventors are pleasantly surprised to find that the silicon-based negative electrode plate does not expand rapidly during actual use.

[0011] The head-to-tail lithium deposition coefficient k of the silicon-based negative electrode plate of the present application is greater than 0.

[0012] Furthermore, the range of r1 value is 0.55~1.67; the range of r2 value is 0.11~3.

[0013] When the r1 value and the r2 value are within the above range, it helps to ensure the uniformity and stability of the electrode material. Since the first coating and the second coating have different lithium ion embedding rates, when the width and thickness difference between the first coating and the second coating is too large, there will be extrusion or gaps at the connection between the first coating and the second coating, which makes it easy for lithium to be deposited.

[0014] Furthermore, by adjusting the thickness and width of the first and second coatings, the pole piece structure can be adjusted, thereby improving the stability of the coating structure to meet the pole piece performance design requirements.

[0015] When the k value satisfies the relationship and range disclosed in the technical solution of the present invention, if the r1 value, r2 value, W1 value and W2 value are further optimized according to the preferred range disclosed in the present invention, the inventors found that the prepared silicon-based negative electrode pole piece not only completely eliminates the edge effect, but also obtains various pole piece structures with various parameter combinations, thereby achieving different electrochemical properties. In actual use, the silicon-based negative electrode pole piece has no rapid expansion phenomenon, and the cold pressing peeling strength is further improved, the stability and integrity of the silicon electrode during the cycle are further improved, the resistance is lower, and the rate is higher.

[0016] Furthermore, the thickness d1 of the first coating layer is 70 μm to 110 μm, and the thickness d2 of the second coating layer is 60 μm to 100 μm.

[0017] The thickness of the first coating layer and the thickness of the second coating layer can be selected within the preferred range disclosed in the technical solution of the present invention. Those skilled in the art can select appropriate thicknesses according to actual needs. For example, the thickness of the first coating layer can be 100 μm, and correspondingly, the thickness of the second coating layer can be 100 μm.

[0018] Furthermore, the width w1 of the first coating layer is 30 mm to 225 mm, and the width w2 of the second coating layer is 75 mm to 270 mm.

[0019] The width of the first coating layer and the width of the second coating layer can be selected within the preferred range disclosed in the technical solution of the present invention. Those skilled in the art can select a suitable width according to actual needs. For example, the width of the first coating layer can be 30 mm, and correspondingly, the width of the second coating layer can be 270 mm.

[0020] Furthermore, the addition ratio W1 of the binder in the first negative electrode slurry is 5% to 15%, and the addition ratio W2 of the binder in the second negative electrode slurry is 5% to 15%.

[0021] The addition ratio of the binder can be selected within the preferred range disclosed in the scheme of the present invention. Those skilled in the art can select a suitable addition ratio according to actual needs. For example, the addition ratio of the binder in the first negative electrode slurry is 10%, and correspondingly, the addition ratio of the binder in the second negative electrode slurry can be 10%.

[0022] Furthermore, the molecular weight of the polyacrylic acid is 10,000 to 20,000, the molecular weight distribution is 1.5 to 6, and the polymerization method is homopolymerization; the molecular weight of the alkali salt of polyacrylic acid is 11,000 to 21,000, the molecular weight distribution is 1.5 to 5, and the polymerization method is homopolymerization.

[0023] The molecular weight, molecular weight distribution, polymerization mode of the polyacrylic acid and the molecular weight, molecular weight distribution, polymerization mode of the alkali salt of polyacrylic acid can be selected within the preferred range disclosed in the technical solution of the present invention, and those skilled in the art can select appropriate molecular weight, molecular weight distribution, and polymerization mode according to actual needs. For example, the molecular weight of the polyacrylic acid can be 10,000, the molecular weight distribution is 1.5, and the polymerization mode is homopolymerization; the molecular weight M2 of the alkali salt of polyacrylic acid can be 11,000, the molecular weight distribution is 1.5, and the polymerization mode is homopolymerization.

[0024] Furthermore, the alkali salt of polyacrylic acid includes one or more of sodium salt of polyacrylic acid, potassium salt of polyacrylic acid and lithium salt of polyacrylic acid.

[0025] The alkali salt of polyacrylic acid can be selected within the preferred range disclosed in the technical solution of the present invention, and those skilled in the art can select the type of alkali salt of polyacrylic acid according to actual needs. The radius of the metal ions in the sodium salt of polyacrylic acid, the potassium salt of polyacrylic acid and the lithium salt of polyacrylic acid are arranged from large to small as potassium, sodium and lithium, and they form ionic bonds similar to hydrogen bonds with the carboxyl functional groups in the main body of the alkali salt of polyacrylic acid and the silicon in the silicon-based material. The smaller the radius of the metal ion, the greater the strength of the ionic bond and the stronger the bonding ability.

[0026] Furthermore, the first negative electrode slurry includes silicon-based active material, graphite, conductive agent and polyacrylic acid; the second negative electrode slurry includes nano silicon, graphite, conductive agent and alkali salt of polyacrylic acid.

[0027] In the technical solution disclosed in the present invention, the silicon-based active material is mainly used to form a silicon matrix. The smaller the silicon-based active material particles are, the better the battery performance is. In order to avoid agglomeration caused by the silicon-based active material particles being too small, graphite is used to support the silicon-based active material particles. The conductive agent is used to make the silicon-based negative electrode plate have conductive properties. Polyacrylic acid and alkali salts of polyacrylic acid are used to bond the silicon-based active material and materials such as graphite to increase the cold pressing peeling strength on the current collector.

[0028] Furthermore, the weight ratio of silicon-based active material: graphite: conductive agent: polyacrylic acid in the first negative electrode slurry is 25-35:45-55:5-15:5-15; the weight ratio of nano-silicon: graphite: conductive agent: alkali salt of polyacrylic acid in the second negative electrode slurry is 25-35:45-55:5-15:5-15.

[0029] The weight ratio of silicon-based active material: graphite: conductive agent: polyacrylic acid in the first negative electrode slurry can be selected within the preferred range disclosed in the technical solution of the present invention, and those skilled in the art can select a suitable weight ratio according to actual needs, such as 30:50:10:10. The weight ratio of silicon-based active material: graphite: conductive agent: alkali salt of polyacrylic acid in the second negative electrode slurry can be selected within the preferred range disclosed in the technical solution of the present invention, and those skilled in the art can select a suitable weight ratio according to actual needs, such as 30:50:10:10.

[0030] Wherein, the silicon-based active material includes at least one of silicon carbon, silicon oxygen, and nano silicon.

[0031] Furthermore, the graphite is natural graphite, and the conductive agent is superconducting carbon.

[0032] The above materials are preferred materials in the technical solution of the present invention.

[0033] The second object of the present invention is to propose a method for preparing the above-mentioned silicon-based negative electrode sheet, comprising the following steps: preparing the first negative electrode slurry; preparing the second negative electrode slurry; applying the first negative electrode slurry to the area where the first coating is located on the current collector, and applying the second negative electrode slurry to the area where the second coating is located on the current collector; processing the coated current collector to obtain the silicon-based negative electrode sheet.

[0034] The preparation method has simple process, convenient and quick operation, cheap raw materials and high cost performance.

[0035] Furthermore, the preparation method further comprises the following steps:

[0036] The preparation steps of the first negative electrode slurry are as follows: adding nano silicon, natural graphite, superconducting carbon and polyacrylic acid in a weight ratio of 25-35:45-55:5-15:5-15 and mixing them evenly;

[0037] The preparation steps of the second negative electrode slurry are as follows: adding nano silicon, natural graphite, superconducting carbon and alkali salt of polyacrylic acid in a weight ratio of 25-35:45-55:5-15:5-15 and mixing them evenly;

[0038] The steps of processing the coated current collector are as follows: baking the coated current collector, cold pressing and striping the current collector during the baking process and then drying it under vacuum, and welding the pole ears to obtain the silicon-based negative electrode plate.

[0039] The preparation method of the first negative electrode slurry and the second negative electrode slurry is simple in process and the raw materials are cheap. The coating process is simple, mature and low in cost. Those skilled in the art can refer to the prior art to select process conditions such as baking temperature, continued drying temperature and time according to actual conditions.

[0040] Furthermore, the alkaline salt of polyacrylic acid is prepared by the following method: an alkaline hydroxide solution with a neutralization degree of 80% is dripped into a polyacrylic acid solution to obtain an alkaline salt solution of polyacrylic acid. The polyacrylic acid of the present application is a high molecular weight substance. By controlling its distribution in the electrode, it helps to control the expansion behavior of the electrode. When the carboxylate groups of polyacrylic acid dissociate, its molecular chain will partially stretch due to the influence of the charge, making the structure of the electrode material more open and easier to diffuse. In order to make the carboxylate groups on the chain dissociate and stretch, the pH value of the acrylate binder solution is controlled by adding an alkaline substance. The pH of the alkaline salt solution of polyacrylic acid is 6 to 7.

[0041] Polyacrylic acid generally exhibits good stability under neutral to alkaline conditions. When the pH of the alkaline salt solution of polyacrylic acid is 6 to 7, it can effectively inhibit the precipitation of lithium at the edge of the electrode surface, thereby extending the cycle life of the battery.

[0042] The preparation method of the alkali salt of polyacrylic acid has simple steps, convenient preparation, mature technology and low cost.

[0043] Furthermore, the alkaline hydroxide includes one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.

[0044] The alkaline hydroxide can be selected within the preferred range disclosed in the present invention, and those skilled in the art can select a suitable type of alkaline hydroxide according to actual needs.

[0045] Beneficial Effects

[0046] Compared with the prior art, the present invention has at least the following beneficial effects:

[0047] The silicon-based negative electrode plate provided by the present invention, wherein the alkaline hydroxyl groups in the alkaline salt of polyacrylic acid can neutralize the carboxyl groups agglomerated in the polyacrylic acid, the carboxyl functional groups can generate hydrogen bonds or covalent bonds with the groups on the silicon surface, can enhance the bonding between silicon particles and between silicon particles and the current collector, the high flexibility of the main chain enables it to withstand the stress caused by the volume change during the lithium extraction and insertion of the silicon-based material, relieve the volume change of the silicon-based material, and is not prone to the shedding of active materials and the cracking of the pole piece, thereby ensuring the stability and integrity of the silicon electrode during the cycle. In addition, the bond formed by the carboxyl group of polyacrylic acid and the silicon-based material, because the carboxyl functional group directly generates hydrogen bonds or covalent bonds with the silicon surface groups, produces a better effect than with polyacrylic acid, which results in a smaller volume change of the second coating, and the lithium ion transmission efficiency of the first coating is lower than the lithium ion transmission efficiency of the second coating, that is, the lithium ion insertion speed of the first coating is lower than the lithium ion insertion speed of the second coating, so the edge lithium precipitation effect of the first coating is suppressed. Since the alkali salt of polyacrylic acid is a low-toxic or non-toxic substance, and polyacrylic acid and the alkali salt of polyacrylic acid are high-molecular substances, they are not easily dissolved in the electrolyte during use but exist in the form of colloid or gel, and there is less pollution during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0049] Figure 1 Schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present invention.

[0050] Wherein: 1-current collector; 2-first coating; 3-second coating; YY direction. DETAILED DESCRIPTION

[0051] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.

[0052] Negative electrode

[0053] The embodiment of the present invention provides a silicon-based negative electrode plate, such as Figure 1 As shown, the silicon-based negative electrode plate includes a current collector 1, and the same surface of the current collector 1 is provided with a first coating 2 and a second coating 3 along the Y direction, the first coating 2 is located on both sides of the second coating 3, the first coating 2 is coated with a first negative electrode slurry, and the second coating 3 is coated with a second negative electrode slurry, the first negative electrode slurry includes polyacrylic acid, and the second negative electrode slurry includes an alkali salt of polyacrylic acid.

[0054] Example 1

[0055] A method for preparing the negative electrode sheet of a lithium ion battery comprises the following steps:

[0056] Preparation of silicon-based negative electrode

[0057] Preparation of the first negative electrode slurry: adding nano silicon, natural graphite, superconducting carbon (Super-P, conductive agent, the same below), and polyacrylic acid (binder, the same below) in a weight ratio of 30:50:10:10 and mixing them evenly to prepare the first negative electrode slurry;

[0058] Preparation of the second negative electrode slurry: adding nano silicon, natural graphite, superconducting carbon, and sodium salt of polyacrylic acid in a weight ratio of 30:50:10:10 to prepare the second negative electrode slurry;

[0059] Coating of negative electrode slurry: controlling the thickness of the first coating to be 100 μm and the width of the coating to be 30 mm, controlling the thickness of the second coating to be 100 μm and the width of the coating to be 270 mm, the first coating and the second coating being located on the same surface of the copper current collector, and the first coating being located on both sides of the second coating, to obtain a pole piece;

[0060] The coated current collector is processed by cold pressing and slitting during drying at 85° C., and then drying at 110° C. for 10 hours under vacuum conditions, welding the tabs, and manufacturing the negative electrode sheet of a lithium-ion battery.

[0061] The lithium ion battery is prepared based on the above negative electrode sheet, comprising the following steps:

[0062] Preparation of positive electrode:

[0063] Lithium cobalt oxide (LiCoO2), superconducting carbon and binder polyvinylidene fluoride (PVDF) are mixed and stirred in a weight ratio of 97.6:1.1:1.3 and evenly coated on the aluminum current collector, and then trimmed, cut into pieces and stripped. After stripping, the positive electrode is dried at 80°C for 10 hours under vacuum conditions, and the pole ears are welded to make the positive electrode sheet.

[0064] Preparation of electrolyte: In a glove box filled with argon, the moisture content is less than 5ppm, the oxygen content is less than 5ppm, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (DEC), and propyl propionate (PP) are mixed in a mass ratio of 1:1:1:2 to obtain an organic solvent. The organic solvent is mixed with lithium hexafluorophosphate (according to the method in the prior art) so that the weight percentage of lithium salt in the electrolyte is 14.5%, thereby obtaining the electrolyte.

[0065] Preparation of the battery:

[0066] An 8μm oil-based diaphragm is selected, and the positive electrode sheet, the diaphragm and the silicon-based negative electrode sheet are wound into a battery cell, the diaphragm is located between the positive electrode sheet and the silicon-based negative electrode sheet, the positive electrode sheet is lead out with an aluminum tab by spot welding, and the silicon-based negative electrode sheet is lead out with a nickel tab by spot welding; then the battery cell is placed in an aluminum-plastic packaging bag, the electrolyte is injected, and a lithium-ion battery is made through processes such as packaging, formation, and capacity division.

[0067] Example 2

[0068] The difference from Example 1 is that the width of the first coating layer is 150 mm, and the width of the second coating layer is 150 mm.

[0069] Example 3

[0070] The difference from Example 2 is that the addition ratio of the polyacrylic acid is 15%, and the addition ratio of the alkali salt of polyacrylic acid is 5%.

[0071] Example 4

[0072] Different from Example 1, the thickness of the first coating layer is 100 μm, and the thickness of the second coating layer is 60 μm.

[0073] Example 5

[0074] The difference from Example 4 is that the addition ratio of the polyacrylic acid is 15%.

[0075] Example 6

[0076] Different from Example 1, the width of the first coating is 225 mm, the width of the second coating is 75 mm, and the thickness is 60 μm.

[0077] Example 7

[0078] The difference from Example 6 is that the addition ratio of the polyacrylic acid is 15%, and the addition ratio of the alkali salt of polyacrylic acid is 5%.

[0079] Example 8

[0080] Different from Example 6, the thickness of the first coating layer is 60 μm, and the thickness of the second coating layer is 100 μm.

[0081] Example 9

[0082] The difference from Example 8 is that the addition ratio of the polyacrylic acid is 5%, and the addition ratio of the alkali salt of polyacrylic acid is 5%.

[0083] Comparative Example 1

[0084] Different from Example 1, the first negative electrode slurry is prepared by using carboxymethyl cellulose (CMC) binder in the same proportion as in Example 1 instead of polyacrylic acid, the first negative electrode slurry is coated on the entire current collector, and the second negative electrode slurry is not coated.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the first negative electrode slurry is coated on the entire current collector, while the second negative electrode slurry is not coated.

[0087] Comparative Example 3

[0088] Different from Example 1, the second negative electrode slurry is coated on the entire current collector, while the first negative electrode slurry is not coated.

[0089] Comparative Example 4

[0090] Different from Example 1, the thickness of the first coating layer is 40 μm.

[0091] Comparative Example 5

[0092] Different from Example 1, the width of the first coating layer is 10 mm, and the width of the second coating layer is 290 mm.

[0093] Comparative Example 6

[0094] Different from Example 1, the width of the first coating layer is 260 mm, and the width of the second coating layer is 40 mm.

[0095] Comparative Example 7

[0096] Different from Example 1, the thickness of the second coating layer is 40 μm.

[0097] Comparative Example 8

[0098] Different from Example 1, the binder used in the first negative electrode slurry is CMC.

[0099] Comparative Example 9

[0100] Different from Example 1, the pH of the alkaline salt solution of acrylic acid is 8.0.

[0101] Comparative Example 10

[0102] Different from Example 1, the thickness of the first coating is 80 μm, the width of the first coating is 50 mm, the thickness of the second coating is 135 mm, the width of the second coating is 225 mm, the addition ratio of polyacrylic acid is 15%, and the addition ratio of the alkali salt of polyacrylic acid is 15%.

[0103] Table 1 shows the indicators and parameters of the embodiments and comparative examples, and Table 2 shows the performance test results of the embodiments and comparative examples.

[0104] Table 1 Indicators and parameters of the embodiments and comparative examples

[0105]

[0106]

[0107]

[0108] Table 2 Performance test results of embodiments and comparative examples

[0109]

[0110] Examples 1 to 6 illustrate that when the indicators of the examples meet the protection scope of the technical solution disclosed in the present invention, the silicon-based negative electrode pole piece does not deposit lithium, the cold pressing peel strength is greater than 9 and the coating is complete, achieving the expected technical effect of the present invention, and by adjusting the thickness and width of the first and second coatings, the pole piece structure can be adjusted, thereby improving the stability of the coating structure to meet the pole piece performance design requirements.

[0111] Examples 2 and 3 illustrate that increasing the addition ratio of the polyacrylic acid binder can improve the cycle performance of the electrode and increase the battery capacity; reducing the addition ratio of the polyacrylic acid alkali salt can further reduce the risk of lithium precipitation.

[0112] Embodiments 1, 2, 4, 6 and 8 illustrate that by adjusting the thickness and width of the main area and the head and tail area of ​​the electrode, the electrode can obtain different electrochemical properties, that is, the design of the electrode performance can be achieved by designing the electrode structure. Embodiment 2 has the best overall performance, with a higher rate and good cycle performance and specific capacity. Embodiment 4 has poor cycle performance and capacity performance, but has the best rate performance. Embodiment 6 has the best cycle performance and the highest specific capacity.

[0113] Example 1 and Comparative Example 1 illustrate that the use of carboxymethyl cellulose adhesive without regional coating will lead to obvious lithium precipitation due to edge effect. This is because the carboxymethyl cellulose adhesive is not a polymer and has poor adhesion. It cannot use the high flexibility of the polymer main chain to withstand the stress of volume change during lithium extraction from silicon-based materials. Moreover, single-area coating cannot use the different strengths of interaction between different adhesives and lithium ions to reduce the lithium ion transmission in the edge area and increase the lithium ion transmission in the middle area. At this time, Comparative Example 1 obviously precipitates lithium, and its cold pressing peel strength is severely reduced compared with Example 1, which ultimately leads to the shedding of the coating after 500 cycles at 25°C. The comparative example cannot achieve the technical effect of the present invention.

[0114] Example 1 and Comparative Examples 2 to 3 illustrate that the use of single-area coating cannot utilize the different interaction strengths between different adhesives and lithium ions to reduce the lithium ion transmission amount in the edge area and increase the lithium ion transmission amount in the middle area. Therefore, whether it is polyacrylic acid or the alkali salt of polyacrylic acid, it will lead to obvious lithium precipitation due to the edge effect, and the cold pressing peel strength of Comparative Examples 2 to 3 is greater than that of Comparative Example 1. This is because the bonding ability of polyacrylic acid and the alkali salt of polyacrylic acid is stronger than that of the carboxymethyl cellulose used in Comparative Example 1. However, Example 1 does not precipitate lithium, while Comparative Examples 2 to 3 obviously precipitate lithium. Comparative Examples 2 and 3 cannot achieve the technical effect of the present invention. The lithium ion embedding speed of the first coating of Comparative Example 2 is low, resulting in the inability of lithium ions to effectively embed into the electrode during high-rate charge and discharge, resulting in lithium precipitation, while the second coating of Comparative Example 3 is prone to lithium precipitation at the edge.

[0115] Example 1 and Comparative Example 4 illustrate that when the coating thickness ratio is lower than the range disclosed in the technical solution of the present invention, the insertion and extraction of lithium ions will be affected due to the thinning of the first coating layer, resulting in lithium deposition due to the edge effect.

[0116] Example 1 and Comparative Example 5 illustrate that when the coating width ratio r2 is lower than the range disclosed in the technical solution of the present invention, the amount of lithium ion transmission may be higher than the capacity of the first coating due to the first coating being too narrow, resulting in lithium deposition due to the edge effect.

[0117] Example 1 and Comparative Example 6 illustrate that when the coating width ratio r2 is higher than the range disclosed in the technical solution of the present invention, the first coating is too wide, resulting in the second coating having a less lithium ion transmission amount than the first coating, which in turn leads to lithium deposition due to the edge effect.

[0118] Example 1 and Comparative Example 7 illustrate that when the coating thickness ratio is lower than the range disclosed in the technical solution of the present invention, the capacity will be reduced due to the thinness of the second coating layer, and the wrapping effect of the alkali salt binder of polyacrylic acid on the active material will be affected, which will eventually lead to the coating falling off after 500 cycles at 25°C, and the technical effect of the present solution cannot be achieved.

[0119] Example 1 and Comparative Example 8 show that using CMC as a binder for the slurry in the head and tail regions has a poor wrapping effect on the silicon negative electrode, a limited effect on alleviating the volume expansion effect of the silicon negative electrode, and a poor effect on improving the edge lithium precipitation effect. Lithium precipitation occurs in high-rate tests, and the coating falls off after 500 cycles at 25°C, and the technical effect of this solution cannot be achieved.

[0120] Example 1 and Comparative Example 9 illustrate that when a PAH alkaline salt with a higher degree of neutralization is used as the binder for the main region, its wrapping effect on the silicon negative electrode begins to decline due to a sharp decrease in the number of carboxyl functional groups in its molecules, and its effect on the volume expansion effect of the silicon negative electrode is limited. After 500 cycles at 25°C, the coating falls off, and the technical effect of this solution cannot be achieved.

[0121] From Comparative Examples 1, 3, 5, 7, 8, and 9, it can be seen that the factors affecting coating shedding are the amount of PAA added and the distribution area of ​​PAA. Beyond the limited range, the designed double coating structure loses its original effect of limiting the lithium ion transmission rate in the head and tail areas, and the volume expansion of the silicon negative electrode during the cycle will cause the coating to fall off. The test methods used in the above embodiments and comparative examples are as follows:

[0122] Performance Test:

[0123] The following tests were performed on the pole pieces and lithium-ion batteries of Examples 1 to 8 and Comparative Examples 1 to 5 respectively:

[0124] (1) Cold press peel strength of negative electrode (180° peel test)

[0125] At room temperature (25℃±2℃), the negative electrode slurry is coated on the surface of the current collector, dried and cold pressed into a pole piece, and the prepared pole piece is cut into a test sample of 20*100mm size. In order to truly restore the bonding force of the pole piece inside the battery, the prepared sample is immersed in the electrolyte for 4h at a temperature of 60℃. After taking it out, wipe the surface with dust-free paper, adhere the side to be tested with double-sided tape, and compact it with a roller to make it completely fit with the pole piece. The other side of the double-sided tape of the sample is pasted on the stainless steel surface, and one end of the sample is bent in the opposite direction with a bending angle of 180°. The high-speed rail tensile machine is used for testing, and one end of the stainless steel is fixed to the lower fixture of the tensile machine, and the bent end of the sample is fixed to the upper fixture. The angle of the sample is adjusted to ensure that the upper and lower ends are in a vertical position, and then the sample is stretched at a speed of 50mm / min until the sample is completely peeled off from the substrate. The displacement and force in the process are recorded. It is generally believed that the force when the force is balanced is the peeling force of the pole piece.

[0126] (2) Standard discharge test

[0127] At room temperature (25℃±2℃), discharge the battery at a given current of 0.2C to a termination voltage of 3.0V, and leave it for 5 minutes; charge the battery at a charging current of 0.5C to 4.45V. When the battery voltage reaches 4.45V, change to 4.45V constant voltage charging with a cut-off current of 0.02C; leave it for 30 minutes; then discharge at a given current of 0.02C to a termination voltage of 3.0V; leave it for 5 minutes; repeat the charge and discharge of the battery twice to obtain the actual discharge capacity of the battery.

[0128] (3) High rate lithium deposition test

[0129] At room temperature (25℃±2℃), let the battery stand for 5 minutes, discharge at 0.2C constant current, cut-off voltage 3.0V; let it stand for 5 minutes, charge to 4.5V at 6.5C constant current and constant voltage, cut-off rate 0.02C; let it stand for 5 minutes, and cycle 50 times according to this standard. After the end, test the battery internal resistance and thickness in turn, and disassemble the battery to check whether there is lithium deposition on the interface. (Thickness change rate is less than 10%)

[0130] (4) Lithium-ion battery cycle performance test

[0131] Place the lithium-ion battery in a 25℃ constant temperature room and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.45V, then charge it at a constant voltage of 4.45V to a current of 0.025C, and then discharge it at a constant current of 0.5C to a voltage of 3.0V. This is a charge and discharge cycle. Repeat the charging and discharging in this way, and calculate the capacity retention rate of the lithium-ion battery after 500 cycles. After 500 cycles, disassemble the interface and observe the surface coating of the negative electrode.

[0132] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A silicon-based negative electrode plate, characterized in that: The silicon-based negative electrode plate includes a current collector, and the same surface of the current collector is provided with a first coating and a second coating along the Y direction, the first coating is located on both sides of the second coating, the first coating is coated with a first negative electrode slurry, and the second coating is coated with a second negative electrode slurry, the first negative electrode slurry includes polyacrylic acid, and the second negative electrode slurry includes an alkali salt of polyacrylic acid.

2. The silicon-based negative electrode plate according to claim 1, characterized in that: The head-to-tail lithium deposition coefficient k of the silicon-based negative electrode plate satisfies the relational expression I, wherein: r1 is the ratio of the thickness d1 of the first coating layer to the thickness d2 of the second coating layer; r2 is the ratio of the width w1 of the first coating layer to the width w2 of the second coating layer, W1 is the addition ratio of the binder in the first negative electrode slurry, and W2 is the addition ratio of the binder in the second negative electrode slurry; The head-tail lithium deposition coefficient k of the silicon-based negative electrode plate is greater than 0.

3. The silicon-based negative electrode plate according to claim 2, characterized in that: The range of r1 values ​​is 0.55~1.67; the range of r2 values ​​is 0.11~3.

4. The silicon-based negative electrode plate according to claim 3, characterized in that: The thickness d1 of the first coating layer is 60 μm to 110 μm, and the thickness d2 of the second coating layer is 60 μm to 270 μm.

5. The silicon-based negative electrode plate according to claim 3, characterized in that: The width w1 of the first coating layer is 30 mm to 225 mm, and the width w2 of the second coating layer is 75 mm to 270 mm.

6. The silicon-based negative electrode plate according to claim 3, characterized in that: The molecular weight of the polyacrylic acid is 10000-20000, and the molecular weight distribution is 1.5-6. The molecular weight of the alkali salt of the polyacrylic acid is 10000-21000, and the molecular weight distribution is 1.5-5.

7. The silicon-based negative electrode plate according to claim 1, characterized in that: The alkali salt of polyacrylic acid includes one or more of sodium salt of polyacrylic acid, potassium salt of polyacrylic acid and lithium salt of polyacrylic acid.

8. The silicon-based negative electrode plate according to claim 1, characterized in that: The first negative electrode slurry comprises a silicon-based active material, graphite, a conductive agent and polyacrylic acid; and the second negative electrode slurry comprises nano silicon, graphite, a conductive agent and an alkali salt of polyacrylic acid.

9. The silicon-based negative electrode plate according to claim 8, characterized in that: The weight ratio of silicon-based active material: graphite: conductive agent: polyacrylic acid in the first negative electrode slurry is 25-35:45-55:5-15:5-15; the weight ratio of nano-silicon: graphite: conductive agent: alkali salt of polyacrylic acid in the second negative electrode slurry is 25-35:45-55:5-15:5-15.

10. The silicon-based negative electrode plate according to claim 8, characterized in that: The silicon-based active material includes at least one of silicon carbon, silicon oxygen, and nano-silicon.

11. A method for preparing a silicon-based negative electrode sheet according to any one of claims 1 to 10, characterized in that: The method comprises the following steps: preparing the first negative electrode slurry; preparing the second negative electrode slurry; coating the first negative electrode slurry on the region where the first coating is located on the current collector, and coating the second negative electrode slurry on the region where the second coating is located on the current collector; and processing the coated current collector to obtain the silicon-based negative electrode sheet.

12. The method for preparing a silicon-based negative electrode sheet according to claim 11, characterized in that: The pH of the polyacrylic acid alkali salt solution is 6-7.

13. The method for preparing a silicon-based negative electrode sheet according to claim 12, characterized in that: The alkaline salt solution of polyacrylic acid is added with one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.

Citation Information

Patent Citations

  • Negative active slurry, battery negative plate and lithium ion secondary battery

    CN117199291A

  • Silicon-based negative electrode plate, fabrication method thereof and lithium ion battery

    CN109888266A

  • Battery negative electrode and electrochemical device comprising same

    CN115663109A

  • Negative pole piece, secondary battery, battery module, battery pack and electric device

    CN116711096A

  • Negative pole piece and battery

    CN118136770A